Estudos Sobre o Potencial do Bambu Guadua angustifolia Kunz. Para a Fitorremediação dos Metais Pesados Zinco e Cádmio. - Barros, Andréa Carla de Almeida (2007)
Phytoremediation is considered to be an economically promising and an ecologically correct technology for the removal of toxic materials from the environment since it employs natural physico-chemical and biochemical processes for the clean up of degraded areas. Guadua angustifolia (Bambusoideae, Poacea), a bamboo that is native in Central and South America and which presents tall, robust and prickly culms, shows considerable potential in the phytoremediation of toxic metals for the following reasons: a) it presents an extraordinary capacity for multiplication and vegetative reproduction; b) it is efficient at fixing CO2 from the atmosphere, thus contributing to the reduction in the socalled 'greenhouse effect'; c) it is not part of the human food chain; d) it presents ornamental traits that can be used to advantage in the landscaping of polluted areas, such as those previously occupied by landfills; and e) the aerial biomass may be used either in civil construction or in the furniture industry after completing its phytoextractive function. The objective of the present study was to investigate the potential of G. angustifolia for the phytoremediation of zinc and cadmium. The absorption and translocation of these metals from roots to leaves, together with their distribution in the different tissues, were analysed. Additionally, the production of metal transporter proteins (phytochelatins) and the formation of complexes between metals and low molecular weight organic compounds were investigated. The experiments were conducted in hydroponic and soil conditions. Soil that had been artificially contaminated with zinc or cadmium sulphate solutions, was distributed in perforated plastic bags. Bamboo shoots, previously maintained in vermiculite, were transplanted to the contaminated soil and kept in the greenhouse at room temperature for 180 days with periodical watering. The washed plants were dried at room temperature and root, culm, leaf and soil samples were digested with a mixture of nitric and perchloric acids (3:1; v/v) for 3 h at room temperature and for 3 4 h at 120°C. The determination of zinc and cadmium in the samples was performed using atomic absorption spectroscopy at 213.9 and 228.8 nm respectively. Based on the absolute average concentration values, the bioconcentration and translocation factors (BCF and TF, respectively) were calculated. The accumulation of metals in organs of the plants cultivated in contaminated soil followed the order roots > culms > leaves. The accumulation of zinc in the roots was 57.2% (2720 mg/kg dry weight), whilst in the aerial parts it was 42.8% (2032 mg/kg). The accumulation vii of cadmium in the roots was 79.9% (770 mg/kg), whilst in the aerial parts it was 20.1% (194 mg/kg). Thus, G. angustifolia fulfils one of the criteria employed to define hyperaccumulator plants in that the concentration of zinc in the aerial parts of plants grown in contaminated substrate was approximately 20.2-fold higher than the average value found in plants grown under control (non-polluted) conditions, whilst the concentration of cadmium was 194-fold higher than the control value. Further analyses showed that the concentration of zinc in contaminated soil that had supported the cultivation of bamboo was reduced by 65.5%, whilst the level of cadmium was reduced by 60.2%. The high values of BCF (> 1) related to zinc indicated that the roots and aerial tissues had not attained saturation and/or that the transport systems were still active under the experimental conditions employed such that even larger quantities of metal could be absorbed and transported. Regarding cadmium, the values of BCF indicated that saturation and/or inactivation of roots had not been attained, as in the case of zinc, whereas this was not valid for the aerial tissues. TF values for both metals were low (< 1) indicating that zinc and cadmium transport in G. angustifolia tissues was not very efficient. One of the greatest obstacles to the use of G. angustifolia in phytoremediation of these metals appears to be related to the translocation in the tissues, mainly from culms to leaves. Although this aspect limits the applicability of G. angustifolia in the phytoremediation of zinc and cadmium, it is clear that this species offers significant potential since the larger portion of its biomass is represented by the culms. Such potential could be exploited by using appropriate agronomic techniques in order to allow the growth of plants in polluted soils, and genetic engineering technology to facilitate the mobility of metals from roots to shoots.